2020
DOI: 10.1101/2020.03.06.979153
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Homologous organization of cerebellar pathways to sensory, motor, and associative forebrain

Abstract: 16Cerebellar outputs take multisynaptic paths to reach higher brain areas, impeding tracing 17 efforts. Here we quantify pathways between cerebellum and contralateral 18 thalamic/corticostriatal structures using the anterograde transsynaptic tracer herpes 19 simplex virus type 1 (H129), the retrograde tracer pseudorabies virus (Bartha), adeno-20 associated virus, and a whole-brain pipeline for neuron-level analysis using light-sheet 21 microscopy. In ascending pathways, sensorimotor regions contained the most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 171 publications
(163 reference statements)
1
38
0
Order By: Relevance
“…In addition, hypoactivation of the PVN in cb δ KO mice can indicate hypothalamic–pituitary-adrenal (HPA) axis dysregulation and chronic stress in cb δ KO animals ( Cohen et al, 2006 ; Kinlein et al, 2015 ; Whitaker and Gilpin, 2015 ). These observations are in line with recent tracing studies ( Fujita et al, 2020 ; Hashimoto et al, 2018 ; Pisano et al, 2020 ) and suggest that altering sensory integration in the input layer can affect numerous circuits throughout the brain.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, hypoactivation of the PVN in cb δ KO mice can indicate hypothalamic–pituitary-adrenal (HPA) axis dysregulation and chronic stress in cb δ KO animals ( Cohen et al, 2006 ; Kinlein et al, 2015 ; Whitaker and Gilpin, 2015 ). These observations are in line with recent tracing studies ( Fujita et al, 2020 ; Hashimoto et al, 2018 ; Pisano et al, 2020 ) and suggest that altering sensory integration in the input layer can affect numerous circuits throughout the brain.…”
Section: Discussionsupporting
confidence: 91%
“…In fact, recent work suggests that the predictive construction of interoceptive signals may be necessary for successful allostasis (Barrett, 2017;Gu & FitzGerald, 2014;Pezzulo et al, 2015). Second, the cortical limbic nodes in both networks, and their points of overlap, have extensive connectivity to subcortical and brainstem structures that are important for allostasis and interoception (Figure 1C) as well as to the cerebellum and the hippocampus, both of which have connections to the structures that process outgoing visceromotor and incoming interoceptive signals (Onat & Çavdar, 2003;Pisano et al, 2021;Suarez et al, 2018;Vertes, 2015). Third, the allostaticinteroceptive system contains portions of motor and pre-motor cortices, consistent with tracttracing evidence that primary motor cortex contains visceromotor maps (Levinthal & Strick, 2012, 2020; this is also consistent with evidence that the anterior mid-cingulate cortex is considered a pre-motor area in the literature on skeletomotor control, and it may be a hub for visceromotor and skeletomotor integration (reviewed in Touroutoglou et al, 2020).…”
Section: The Brain's Intrinsic System For Allostasis and Interoceptionmentioning
confidence: 99%
“…Although the conditioned response of PCs after fear conditioning has not been reported, the decreased output of PCs in STAT3 PKO mice may disinhibit the activity of deep cerebellar nuclei (DCN), and DCN may send neural signals to other fear-related regions ( Figure 7 ). Recently, it has been identified that the cerebellum has pathways to sensorimotor, associative, and modulatory forebrain ( Pisano et al, 2020 ). As previous studies showed, fear memory network is distributed in the forebrain ( Wager et al, 2015 ; Tovote et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%